The relationship between mother's knowledge and the incidence of stunting in toddlers in polindes, mundar village, south labuan amas district, hulu sungai tengah regency in 2024 - Qomah, Isti; Tazkiah, Misna; Rahmayanti, Rizka (Surya Hijau Manfaat, 2024)
Stunting is stunted growth caused by a lack of nutritional intake due to a diet that does not meet long-term needs. South Kalimantan Province is in the top 3 provinces with the highest reduction in stunting (-5.4%) in 2022 based on the SSGI results released by the Indonesian Ministry of Health. Initially in 2021 stunting in South Kalimantan reached 30.0% and in 2022 it decreased by 24.6%. With a figure of 24.6%, reducing stunting is still a priority for South Kalimantan to achieve the target of 14% in 2024. Based on data from the Hulu Sungai Tengah district health service in 2020, the figure was 10%, experiencing a decrease in 2021 with a figure of 9.44%, and in in 2022 there will be an increase of 31.10%. This research is analytical research. With a Cross Sectional approach. The research results showed that the majority of mothers had sufficient knowledge and 21 children were not stunted (33.9%), 9 children were stunted (14.5%), and there was insufficient knowledge with the incidence of stunted children being 13 people (21.0%). and there were 2 children (3.2%) who were not stunted, while there were 0 people (0%) with good knowledge and stunted babies, and 17 people (27.4%) who were not stunted. Based on the results of the chi square test, it was found that there was a relationship between maternal knowledge and the incidence of stunting at the Mundar Village Polindes with a P value = 0.000. It is recommended that the Mundar Village Polindes, South Labuan Amas District, Hulu Sungai Tengah Regency further increase health education activities related to health and education for mothers with babies and toddlers about preventing stunting through improving child nutrition.